2000
DOI: 10.1109/4233.897063
|View full text |Cite
|
Sign up to set email alerts
|

Hadamard-based image decomposition and compression

Abstract: In this paper, we develop a general algorithm for decomposition and compression of grayscale images. The decomposition can be expressed as a functional relation between the original image and the Hadamard waveforms. The dynamic adaptive clustering procedure incorporates potential functions as a similarity measure for clustering as well as a reclustering phase. The latter is a multi-iteration, convergent procedure which divides the inputs into nonoverlapping clusters. These two techniques allow us to efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…As for the required computational complexity, it has been shown that the proposed N-point complex-valued CS-SCHT algorithm requires log N complex additions/subtractions and /2 1 multiplications by . x (15) x (1) x (14) x (2) x (13) x (3) x (12) x (4) x (11) x (5) x (10) x (6) x (9) x (7) x ( …”
Section: Discussionmentioning
confidence: 99%
“…As for the required computational complexity, it has been shown that the proposed N-point complex-valued CS-SCHT algorithm requires log N complex additions/subtractions and /2 1 multiplications by . x (15) x (1) x (14) x (2) x (13) x (3) x (12) x (4) x (11) x (5) x (10) x (6) x (9) x (7) x ( …”
Section: Discussionmentioning
confidence: 99%
“…In addition, high-performance and low-cost imaging devices are highly desired for THz beam visualization for scientific metrology applications such as quasi-optical system alignment, quantum-cascade laser (QCL) design and op-timization [9], and THz antenna characterization [10]. To date, the THz imaging systems that have been demonstrated generally fall into one of three categories: (1) single-element imagers that obtain images by mechanical scanning, (2) array imagers [e.g., focal-plane arrays (FPAs)] that consist of an array of imaging sensor elements [6]- [8], and (3) coded-aperture imaging (CAI) using two-dimensional aperture masks [11]- [14]. In many applications, important events happen on the scale of microseconds, making imaging by mechanical scanning impractical due to the inherently low frame rates.…”
Section: Introductionmentioning
confidence: 99%
“…Effros et al [14] demonstrate both the failures and the successes of the KLT. Other transforms, such as DCT [38,25,32], DFT [40], Hadamard transform [36], Slant transform [20] are computationally faster than the KLT, while exhibiting slightly worse performance than that of the KLT, in terms of energy compaction and decorrelation. Among them, DCT is the most widely used for image compression.…”
Section: Introductionmentioning
confidence: 99%